Switched capacitor-based continuous input current high step-up impedance source dc-dc converter - Ahmad A.; Shiluveru K.; Singh R.K. (My University, 2025)
The conventional converter needs to be operated at a high duty cycle to achieve maximum possible voltage gain. This leads to severe reverse recovery of switches, increases losses, and reduces efficiency. This study presents a modified switched-capacitor-based high gain continuous input current quasi-Z-source converter (qZSC) for DC microgrid applications. The proposed converter utilises the embedded switched-capacitor techniques and can give a high voltage gain with a low duty ratio compared to the conventional converters. The proposed converter also experiences less capacitor voltage and inductor current stresses compared to the conventional Z-source converters. This facilitates the use of lower-rated capacitors and inductors for higher power applications. Detailed steady-state, small-signal, and power loss analysis of proposed qZSC is discussed in this study. A prototype of 100 W is designed and implemented using TI TMS320F28335 Experimenter Kit to verify the operation of the proposed converter. © The Institution of Engineering and Technology 2020.